2020
DOI: 10.1038/s41598-020-72639-7
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of synaptic plasticity and novel object recognition in the hypergravity-exposed rats

Abstract: The gravity is necessary for living organisms to operate various biological events including hippocampus-related functions of learning and memory. Until now, it remains inconclusive how altered gravity is associated with hippocampal functions. It is mainly due to the difficulties in generating an animal model experiencing altered gravity. Here, we demonstrate the effects of hypergravity on hippocampus-related functions using an animal behavior and electrophysiology with our hypergravity animal model. The hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…23 A 4 g hypergravity condition for 4 weeks could impair synaptic efficacy and long-term potentiation in CA1 neurons of the hippocampus along with the poor performance of a novel object recognition task. 24 A 2 g hypergravity condition during preweaning specifically suppressed vestibular-related stress responses. 25 In this study, our results showed that 7.0-33.0 T SMF exposure for 1 h did not have severe impacts on food and water consumption, body and organ weight, blood composition and chemistry, or histomorphology of the major organs in mice.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…23 A 4 g hypergravity condition for 4 weeks could impair synaptic efficacy and long-term potentiation in CA1 neurons of the hippocampus along with the poor performance of a novel object recognition task. 24 A 2 g hypergravity condition during preweaning specifically suppressed vestibular-related stress responses. 25 In this study, our results showed that 7.0-33.0 T SMF exposure for 1 h did not have severe impacts on food and water consumption, body and organ weight, blood composition and chemistry, or histomorphology of the major organs in mice.…”
Section: Discussionmentioning
confidence: 91%
“…Simulated microgravity also delayed ossification manifests during zebrafish development 23 . A 4 g hypergravity condition for 4 weeks could impair synaptic efficacy and long‐term potentiation in CA1 neurons of the hippocampus along with the poor performance of a novel object recognition task 24 . A 2 g hypergravity condition during preweaning specifically suppressed vestibular‐related stress responses 25 …”
Section: Discussionmentioning
confidence: 99%
“…A major advantage of the task is that it can be used in both rats and mice (Agarwal et al, 2020;Chang et al, 2020). Current iterations of the NOR paradigm are widely used to study memory (Cole et al, 2020), synaptic plasticity (Lee et al, 2020), impairment and/or recovery of function in brain disease (Grayson et al, 2015), TBI (Amoros-Aguilar et al, 2020), stress (Brivio et al, 2020;Glushchak et al, 2021), aging (Amirazodi et al, 2020), sleep (Shahveisi et al, 2020), autism (Batista et al, 2019;Gandhi and Lee, 2020), and epigenetics (Ellis et al, 2020;Sadat-Shirazi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is noticeable that the effects of centrifugation are only partially described in humans [18][19][20][21][22]. Like during microgravity exposure, hypergravity exposure, from 1.5 to 5 g, affects the vestibular functions [23][24][25][26] and modifies gene expression in the brain [27][28][29] and cognitive performances [30][31][32]. The use of hypergravity by centrifugation is required to qualify the biological effects of space motion sickness.…”
Section: Introductionmentioning
confidence: 99%